Wood destroying fungi / Md Zulkifli Mohammad - Mohammad, Md Zulkifli (2007)
Fungi is a type of wood destroying agent, since 19th century, many scientist made researches to destroy fungi. The wood destroying fungi research is known as wood mycology. Wood mycology is the research of fungi that attacks and grow on sawn timbers. This research is to give simple explanation of the common fungi found on wood surface. Three species of common is brown-rot fungi, white-rot fungi and soft rot fungi. Besides, there are research on the characteristics of wood destroying fungi. The treatment methods were also searched to assure that these fungi gone from the wood. Fungi also give a lot of effects to manufacturing economy, no wonder many scientists do research on fungi until today.